THE INFLUENCE OF INDEPENDENT COMMISSIONERS, AUDIT QUALITY, AND FINANCIAL DISTRESS ON EARNINGS MANAGEMENT - Seto Aji Sampurno; Dwi Kismayanti Respati; Santi Susanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
Earnings management is a series of actions taken by company management to increase reported earnings in a certain accounting period, without corresponding growth in the company's long-term earnings. This is done by managers to satisfy personal interests or boost the market value of the company so that it will look profitable for users of financial information. This study aims to empirically examine the effect partially and simultaneously between the independent variables of independent commissioners, audit quality, and financial distress with the dependent variable of earnings management. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2022. The sampling technique used is simple random sampling method with the final sample being 100 sample companies with a total of 200 observational data. The data analysis technique in this study used multiple linear regression analysis and the data was processed with the help of the SPSS Version 25 program. The results of this study indicate that independent commissioners partially had a significant negative effect on earnings management, audit quality partially had no effect on earnings management, and financial distress partially had a significant positive effect on earnings management. The results of research by independent commissioners, audit quality, and financial distress simultaneously have an influence on earnings management.